Latitude‐wide genetic patterns reveal historical effects and contrasting patterns of turnover and nestedness at the range peripheries of a tropical marine fish. Issue 12 (19th March 2015) - Liggins, Libby; Booth, David J.; Figueira, Will F.; Treml, Eric A.; Tonk, Linda; Ridgway, Tyrone; Harris, David A.; Riginos, Cynthia
Abstract : Few studies have examined core–periphery genetic patterns in tropical marine taxa. The core–periphery hypothesis (CPH) predicts that core populations will have higher genetic diversity and lower genetic differentiation than peripheral populations as a consequence of greater population sizes and population connectivity in the core. However, the applicability of the CPH to many tropical marine taxa may be confounded by their complex population histories and/or high (asymmetric) population connectivity. In this study we investigated genetic patterns (based on mtDNA) across the latitudinal range of the neon damselfish Pomacentrus coelestis (36°N, Japan – 37°S, east Australia). We suggest a novel hypothetical framework for core–periphery genetic patterns and extend typical analyses to include genealogical analyses, partitioned β‐diversity measures (total βSOR, turnover βSIM, and nestedness‐resultant βSNE ), and analyses of nestedness. We found that the existence of two divergent lineages of the neon damselfish led levels of genetic diversity to deviate from CPH expectations. When focusing on the widespread lineage (Pacific clade) nucleotide diversity was higher in the core, supporting the CPH. However, genetic patterns differed toward the northern and southern peripheries of the Pacific clade. The turnover of haplotypes (pairwise‐βsim ) increased over distance in the north, indicative of historical colonization with little contemporary migration. In contrast, although turnover was still dominant in the south (βSIM ), there was no relationship to distance (pairwise‐βsim ), suggesting the influence of more contemporary processes. Moreover, the haplotype compositions of populations in the south were nested according to latitude, indicating immigration from lower latitudes toward the southern periphery. By extending the typical characterizations of core–periphery genetic patterns we were able to identify the effects of lineage sympatry on measures of genetic diversity and contrasting demographic histories toward the latitudinal peripheries of the neon damselfish's range.